2013
DOI: 10.1089/acm.2011.0885
|View full text |Cite
|
Sign up to set email alerts
|

“I'm More in Balance”: A Qualitative Study of Yoga for Patients with Chronic Neck Pain

Abstract: Participants linked yoga to change on all dimensions of human experience, attributing reduced pain levels, increased coping ability, better pain acceptance and increased control to it. Body awareness appeared a key mechanism in these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 32 publications
4
60
0
Order By: Relevance
“…For example, Tul et al interviewed chronic pain patients in Canada 33 and Cramer et al analyzed participant interviews after a yoga program for chronic neck pain in Germany. 34 Both studies reported body awareness, pain acceptance, and increased control over health as major themes discussed by participants. Furthermore, participants with chronic neck pain perceived improved coping mechanisms and reflected on the social benefits of yoga.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Tul et al interviewed chronic pain patients in Canada 33 and Cramer et al analyzed participant interviews after a yoga program for chronic neck pain in Germany. 34 Both studies reported body awareness, pain acceptance, and increased control over health as major themes discussed by participants. Furthermore, participants with chronic neck pain perceived improved coping mechanisms and reflected on the social benefits of yoga.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, participants with chronic neck pain perceived improved coping mechanisms and reflected on the social benefits of yoga. 34 Given the limited qualitative literature on yoga for chronic pain conditions, it is unclear if participants with cLBP would have distinct experiences different from those with other types of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Here, as well as in previous studies, yoga supported individuals in developing enhanced awareness of stress-related bodily sensations and strategies to effectively cope. 9,14 Overall participants in yoga treatment report greater self-efficacy and the capacity to regulate symptoms irrespective of health condition. This is demonstrated by a range of recent studies on the effects of yoga for a minority population with lower back pain and stress-related symptoms, as a treatment for smoking cessation among women, and as a treatment to help an elderly population regain balance self-efficacy after a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…12 While mind-body practices may offer vast benefits for PTSD, few studies explore the qualitative perceptions of those participating in yoga treatment. 8,13,14 To our knowledge, no studies have investigated the experiences of yoga treatment for patients suffering from PTSD. Rather than evaluating the effectiveness of yoga, the primary objective of the current study was to understand the experiences of participants with PTSD symptoms partaking in traumasensitive KY treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective experiences can be better approached with qualitative studies, as evidenced by the study using narratives to identify the perception of yoga practitioners during an experience of cervical pain [24]. For the qualitative component of the study, the participants were given a trigger question ("which changes do you expect to perceive in yourself with the yoga practice?")…”
Section: Mantramentioning
confidence: 99%